The relationship between protein-energy wasting and cognitive impairment in patients receiving maintenance hemodialysis - Jun Liu; Jingfang Wan; Kehong Chen; Yani He; Weiwei Zhang; Jiyuan Luo; Dan Li (Frontiers in Neurology)
ObjectivesTo investigate the relationship between protein-energy wasting (PEW) and cognitive impairment (CI) in patients undergoing maintenance hemodialysis (MHD).MethodsA total of 185 patients undergoing MHD between June 2020 and April 2022 were initially recruited. Among the initially recruited patients, 25 patients were excluded, and 160 patients were finally involved in this study. The Montreal Cognitive Assessment-Basic (MoCA-B) was utilized to assess patients’ cognitive functions. Patients were categorized into two groups based on the presence or absence of PEW as per the diagnostic criteria. The severity of PEW was evaluated using the Scored Patient-Generated Subjective Global Assessment (PG-SGA) and Malnutrition Inflammation Score (MIS). Baseline data, PEW-related indicators, and cognitive function scores were compared between the CI and non-CI groups. Logistic regression analysis was employed to identify the factors influencing CI in patients undergoing MHD.ResultsThere were significant differences between the two groups in terms of age, educational level, Kt/V, PEW detection rate, PEW-related indicators [albumin (ALB)], lean body mass, arm muscle circumference (AMC), normalized dietary protein intake (nDPI), PG-SGA score, and MIS score (p < 0.05). The MoCA-B scores of MHD patients with PEW were significantly lower than those of patients without PEW (p < 0.05). The two groups exhibited significant differences in executive function, orientation, abstraction, delayed recall, and attention scores (p < 0.05). Multivariate logistic regression analysis indicated that age, PEW severity, Kt/V, and ALB were significant influential factors of CI in patients undergoing MHD (p < 0.05).ConclusionPEW was closely associated with CI in patients undergoing MHD. Those combined with PEW were more likely to develop CI, and to suffer from more severe CI. Active precautionary measures should be taken against PEW to delay the progression of CI in patients undergoing MHD.